Evaluating the Nature of Distractive Driving Factors towards Road Traffic Accident - Khawar Khan; Syed Bilal Zaidi; Asad Ali (Salehan Institute of Higher Education, 2020)
For past two decades many researchers have been working on quantitative as well as qualitative study of distractive driving using different approaches. Road traffic accidents have been identified as the main source of human casualties and cause of damages to the economy and society, as millions of humans is killed every year in these accidents around the world. National-level studies in Pakistan reveal that a higher percentage of males in the age group from twenty to forty years lose their lives in road traffic accidents when compared with that of females. Due to these factors, it is alarming for a society, which is highly dependent on males such as Pakistan, as these losses put numerous families into the financial crisis that lead to poverty. This study envisaged identifying whether moods and emotions play any role in road traffic accidents of young drivers. The study reviews have shown various gaps in our understanding. For this purpose, qualitative interviews of young drivers who are university going and have met some road accidents in recent years in Pakistan had been conducted. Data from the interviews had been transcribed for analysis while maintaining the anonymity of the participants for confidentiality. Analysis of the transcribed data reveals various factors that contribute to road traffic accidents where major causes are distractions, different weather conditions, sleep deprivation, unsafe lane changes, night-time driving, and these factors are triggered by the behavior when youthful drivers engage in driving for sensation seeking and self-esteem. We conclude that it is just through the appropriation of a systems approach that coordinated countermeasures can be proposed and actualized to relieve driver mistakes caused by distraction.